Uncertainty, pastoral knowledge and early warning: A review of drought management in the drylands, with insights from northern Kenya - Derbyshire, Samuel F.; Banerjee, Rupsha R.; Mohamed, Tahira Shariff; Roba, Guyo Malicha (Frontiers Media, 2024)
This article explores the recent history of early warning systems in Kenya, determining key features of the entangled political, technical and conceptual processes that prefigure contemporary drought management there. In doing so, it draws out wider implications regarding drought and anticipatory action across Africa’s drylands, considering the friction between the dynamics of disaster risk management that structure formal early warning systems and those that shape pastoralist engagements with the volatile and uncertain worlds they inhabit. Surveying recent literature on pastoralism’s unique relationship with uncertainty, and associated forms of networked, relational resilience, it reflects on some of the inherent limitations of current approaches to “local knowledge” in the humanitarian sphere. In doing so, it emphasises the need for new, creative approaches to early warning and anticipatory action, which are not merely established via the external synthesis of data but are rather oriented around local pastoralist drought preparation and mitigation strategies and comprise enough flexibility to adapt to a fast-shifting terrain of challenges and possibilities.